Coupled dissolution and precipitation at the cerussite-phosphate solution interface: Implications for immobilization of lead in soils - Wang, L.; Putnis, Christine; Ruiz-Agudo, E.; King, H.; Putnis, Andrew (2013)
In situ atomic force microscopy (AFM) has been used to study the interaction of phosphate-bearing solutions with cerussite, PbCO3, (010) surfaces. During the dissolution of cerussite we observed simultaneous growth of needle-shaped or spherical pyromorphite phases. This occurred at two different pH values and ionic strengths relevant to soil solution conditions. The initial dissolution processes occurring at the cerussite solid-phosphate solution interface were clearly distinguished, and heterogeneous nucleation and growth rates of pyromorphites at phosphate concentrations ranging from 0.1 µM to 10 mM were quantitatively defined. Enhanced cerussite dissolution in the presence of high salt (NaCl or NaF) concentrations leads to an increase in pyromorphite nucleation and growth rates. The newly formed pyromorphites were found to be stable upon contact with water or citrate-bearing solutions under acidic or alkaline conditions in the pH range 4-8. These in situ observations may improve the mechanistic understanding of processes resulting in lead immobilization in diverse soil systems as well as to enhance the effectiveness of phosphate-based treatments for remediation of lead-polluted soils.